ChemInform Abstract: Total Syntheses of Hyperforin and Papuaforins A—C, and Formal Synthesis of Nemorosone Through a Gold(I)‐Catalyzed Carbocyclization. Issue 1 (January 2015) - Bellavance, Gabriel; Barriault, Louis
Abstract The total syntheses of the polyprenylated polycyclic acylphloroglucinols hyperforin (VI) and papuaforins A—C (III)‐(V), and the formal synthesis of nemorosone (VII) are reported.